2011
DOI: 10.1007/s10741-010-9213-3
|View full text |Cite
|
Sign up to set email alerts
|

Current and future role of cardiovascular magnetic resonance in cardiac resynchronization therapy

Abstract: Cardiac resynchronization therapy (CRT) has revolutionized the treatment of selected patients with systolic heart failure. It is well recognized, however, that the symptomatic response to and the outcome of CRT is highly variable. The degree of pre-implant mechanical dyssynchrony and the extent as well as the localization of myocardial scarring are known to contribute to this variability. Cardiovascular magnetic resonance (CMR) is the gold-standard imaging modality for the assessment of myocardial structure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…29 An increase in LVEF above 7.5% during low-dose dobutamine echocardiography exhibited a sensitivity of 76% and a specificity of 86% in predicting response to CRT. 30 The burden and the transmural extension of myocardial scar measured by cardiovascular MRI have been shown to be associated with a poor response rate to CRT, 31 similar to a high scar burden quantified by single photon emission computed tomography myocardial perfusion imaging. 32 Other clinical, electromechanical and electrophysiological issues before device implantation have been identified by Mullens et al 29 In the present study, we demonstrated that metabolomic is unable to predict the outcome of CRT patients: NOESY, CPMG and DIFF spectra for both serum and urine samples showed very low discrimination accuracy (from 43.7 to 50.8%) that precludes its use in common clinical practice.…”
mentioning
confidence: 92%
“…29 An increase in LVEF above 7.5% during low-dose dobutamine echocardiography exhibited a sensitivity of 76% and a specificity of 86% in predicting response to CRT. 30 The burden and the transmural extension of myocardial scar measured by cardiovascular MRI have been shown to be associated with a poor response rate to CRT, 31 similar to a high scar burden quantified by single photon emission computed tomography myocardial perfusion imaging. 32 Other clinical, electromechanical and electrophysiological issues before device implantation have been identified by Mullens et al 29 In the present study, we demonstrated that metabolomic is unable to predict the outcome of CRT patients: NOESY, CPMG and DIFF spectra for both serum and urine samples showed very low discrimination accuracy (from 43.7 to 50.8%) that precludes its use in common clinical practice.…”
mentioning
confidence: 92%
“…In a canine model of LBBB, the proposed method shows good correlation with tagged MRI, which can be considered the reference standard for myocardial motion analysis. The use of MRI in the context of CRT delivery presents advantages over echocardiography, especially for ischemic heart disease, as late gadolinium enhancement imaging allows avoiding LV lead deployment in the scarred myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Despite no CMR criteria suggested by the heart failure guideline published in 2012, 104) CMR-based ICD therapy seems to hold promise in the prediction of patients who may benefit from ICD therapy. The same strategy can be true for determining potential candidates of cardiac resynchronization therapy (CRT) or for planning CRT procedures, [135][136][137] but this has yet to be confirmed with more data.…”
Section: )mentioning
confidence: 99%